Esensi Perpustakaan Sebagai Jantung Perguruan Tinggi: Ditinjau Berdasarkan Perspektif Mahasiswa Difabel UIN Sunan Kalijaga - Ramadhani Ginting (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2020)
The heart of higher education is an idiom that is often pinned to libraries because of the large role of libraries as a place to find and obtain valid and relevant information. In addition, the library also serves as a lifelong learning place. Thus, the library is mandated by the state through Law Number 43 of 2007 in order to be able to provide rights in accessing and obtaining information in a balanced, equal and even manner based on the needs of its users, both physically healthy users and users who are declared persons with difables. Thus, even people with difables can feel the library as the heart of higher education and as a first solution in overcoming problems related to their higher education.This study uses a qualitative descriptive method, with data obtained from interviews with difables students of UIN Sunan Kalijaga and literature studies. The results of this study indicate that the library of UIN Sunan Kalijaga is able to act as the heart of higher education for disabled students, in terms of implementation and implementation of objectives, functions, completeness of learning resources, equality and evenness in accessing and obtaining information, procurement of adaptive facilities and infrastructure.